2021
DOI: 10.2991/assehr.k.210305.096
|View full text |Cite
|
Sign up to set email alerts
|

Prototype of Science Literacy Instruments on the Competence of Construction and Property Technology Expertise

Abstract: This study aims to develop a prototype of a mechanical scientific literacy instrument for vocational students on the competence of construction technology and property expertise. The type of research used in this research is the Research and Development method (R&D). This research was conducted from January to February 2020. Based on expert judgment, this scientific literacy instrument can be said to be fit for use both in content and construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Where the OECD ( 2009) has a focus on PISA assessment in the development of youth competencies which is then complemented by the OECD (2012) related to PISA measurements of mathematical abilities and students' problem solving on simple problems that are aligned with the principles of literacy for vocational education coupled with in that year range, there are many research discussions related to the sustainable construction sector so that the combination of both give rise to superior charts for the 2008 -2012 range. From the table above, there is an interesting thing, in the range of 2013 -2017 and 2018 -2023 where the number of publications obtained the same value as the acquisition of a slightly different number of citations, even so it was found that although the graph tends to decrease, the research has focused more on integrating literacy into the learning of Vocational High School students in the Field of Building Construction Rouf et al, 2021) such as the development of teaching materials (Maulana et al, 2022) and the analysis of the suitability of current literacy for students of Vocational High School in the Field of Building Construction .…”
Section: Figure 3 Growth Trend Graphicsmentioning
confidence: 95%
“…Where the OECD ( 2009) has a focus on PISA assessment in the development of youth competencies which is then complemented by the OECD (2012) related to PISA measurements of mathematical abilities and students' problem solving on simple problems that are aligned with the principles of literacy for vocational education coupled with in that year range, there are many research discussions related to the sustainable construction sector so that the combination of both give rise to superior charts for the 2008 -2012 range. From the table above, there is an interesting thing, in the range of 2013 -2017 and 2018 -2023 where the number of publications obtained the same value as the acquisition of a slightly different number of citations, even so it was found that although the graph tends to decrease, the research has focused more on integrating literacy into the learning of Vocational High School students in the Field of Building Construction Rouf et al, 2021) such as the development of teaching materials (Maulana et al, 2022) and the analysis of the suitability of current literacy for students of Vocational High School in the Field of Building Construction .…”
Section: Figure 3 Growth Trend Graphicsmentioning
confidence: 95%